Tabarru’ Fund Sharia Insurance Using The 2019 Mortality Table, Mortality Law and Cost of Insurance Method - Wulandari, Fitria Sisca; Fauziah, Irma; Fitriyati, Nina (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The sharia life insurance program has two ways of managing funds, namely involving a savings element and not involving a savings element. Programs that do not involve a savings element do not have a clear division of tabarru’ funds that must be paid participant so it is the company's job to calculate it . In calculating the percentage of tabarru' funds used method Cost of Insurance (COI) . The COI method is method for calculating tabarru’ funds  with using several parameters, namely mortality tables , investment value , management fees and discount factors . In this research, we will discuss how to obtain tabarru' funds using the 2019 Indonesian mortality table and the 2019 Indonesian mortality table with the Gompertz mortality law, Makeham mortality law and De Moivre mortality law. with method Cost of Insurance . Based on the case illustration, the results show that the tabarru' funds that must be paid by participants are directly proportional to the participant's age, management fees and insurance money, but inversely proportional to the investment value. Tabarru' funds will be greater if using the De Moivre mortality table so this can be a consideration for the company while the Makeham mortality table can be a consideration for participants.